Does environmental public policy act as a slowdown for urban expansion? A 2012-2023 analysis with Landsat images - Jorge Alberto Escandón-Calderón; Columba Jazmín López-Gutiérrez; Demian Vázquez-Muñoz; Marco Antonio Gálvez-Lomelín; Marcela Rosas-Chavoya (Revista de Teledetección)
Urban expansion constitutes one of the main activities that modify natural environments worldwide; the most vulnerable areas to these effects are peri-urban areas. An example is 59% of the surface of Mexico City, considered a Conservation Zone (CZ). Within the CZ there are natural ecosystems, agricultural and livestock activities take place, which is why it is considered an area that provides a large number of services, including ecosystem services. This study aimed to analyze the rates of urban expansion in the CZ during two periods (2012-2018, 2018-2023) with contrasting environmental policies. Landsat 7 and 8 images were used to perform a supervised classification with Random Forest algorithm with which the surface of different land use classes was estimated for three years 2012, 2018, and 2023. The dynamics of urban expansion in two administrative periods were evaluated with different approaches and budget priorities in the environmental public policy of the CZ. Supervised classification had adequate accuracy (≥89%). The rate of urban expansion during the studied periods was 31.7% (269 ha/year) from 2012 to 2018 and 16.9% (190.3 ha/year) from 2018 to 2023. A clear deceleration of land use change for urban purposes was observed; three out of the nine municipalities comprising the SC exhibited an urban expansion rate close to 0%. Additionally, a “protective” effect was also exhibited towards the agricultural areas and primary forests of the CZ. The budget increase focused on environmental conservation activities and rural development of the CZ appears to have affected the dynamics of urban expansion in the peri-urban area of one of the most complex cities in the world.